2019
DOI: 10.1016/j.antiviral.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

VER-155008 induced Hsp70 proteins expression in fish cell cultures while impeding replication of two RNA viruses

Abstract: The heat-shock protein 70 (Hsp70) inhibitor, VER-155008 (VER), was explored as a potential antiviral agent for two RNA viruses important to fish aquaculture, viral hemorrhagic septicemia virus (VHSV) and infectious pancreatic necrosis virus (IPNV). Studies were done at a temperature of 14 °C, and with cell lines commonly used to propagate these viruses. These were respectively EPC from fathead minnow for VHSV and CHSE-214 from Chinook salmon embryo for IPNV. Additionally, both viruses were studied with the Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…To overcome the confounding effects of functional redundancy between Hsc70 and Hsp70 and further examine at which stages of the viral life cycle their involvement is needed, we first employed two inhibitors of Hsp70s, VER155008 (Pham et al., 2019) and quercetin (Chen et al., 2022; Ogawa et al., 2014) to inhibit Hsc70 and Hsp70 simultaneously. Cell viability assays indicated that 40 μM quercetin and 2 μM VER155008 had no cytotoxicity in WRD cells (data not shown), and the concentrations were used for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the confounding effects of functional redundancy between Hsc70 and Hsp70 and further examine at which stages of the viral life cycle their involvement is needed, we first employed two inhibitors of Hsp70s, VER155008 (Pham et al., 2019) and quercetin (Chen et al., 2022; Ogawa et al., 2014) to inhibit Hsc70 and Hsp70 simultaneously. Cell viability assays indicated that 40 μM quercetin and 2 μM VER155008 had no cytotoxicity in WRD cells (data not shown), and the concentrations were used for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…This molecule shows potent anticancer activity as well as antiviral properties (Baquero-P erez & Whitehouse 2015). This compound was tested against VHSV and IPNV in fish cell lines, and the results revealed that the replication of both viruses was significantly reduced by VER-155008 (Pham et al 2019). On the other hand, geldanamycin, with affinity for the ATPbinding pocket of HSP90, also shows antitumour and antiviral properties (Li et al 2010a).…”
Section: Protein Synthesis Post-translational Modifications Virion As...mentioning
confidence: 99%
“…The Hsp70 is thus predicted to act as a broad‐spectrum antiviral target (Shan et al, 2018). Although a drug targeting Hsp70 function has been investigated with two fish viruses, viral haemorrhagic septicaemia virus (VHSV) and infectious pancreatic necrosis virus (IPNV) (Pham et al, 2019), no antiviral potential of any drugs targeting Hsp70 expression had been tested against any aquatic animal virus till now (Pham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%